Research on anthrax toxin analysis based on big data mining technology. Issue 1 (January 2021) - Chen, Jingfei; Li, Hexi; Jiang, Huaning; Liang, Ting
Abstract: Anthrax is still endemic in some areas around the world, and a large number of people and livestock are at risk of contracting anthrax. As the pathogenic substance of Bacillus anthracis, anthrax toxin plays an essential pathogenic role. Researchers have conducted detailed studies and reports on their genes, structures, and biological activities. However, few articles analyse the field from the perspective of bibliometrics. In the present study, we used bibliometric software such as Citespace to examine the literature data and aimed to provide a reference for researchers in this field. In terms of journals, P NATL ACAD SCI USA, INFECT IMMUN and J BIOL CHEM rank among the top 10 as to the number of published articles and the number of co-citations, and they have an important influence in the field of anthrax toxins. As for researchers, the quantity and quality of the articles published by the three researchers, LEPPLA SH, MOAYERI M, and COLLIER RJ, have advantages. Their research on anthrax toxin is worthy of attention. On the frontiers of research, future research may have various directions, such as the in-depth explanation of the mechanism of anthrax toxin-induced diseases, how to use anthrax toxin to enhance anti-tumour methods to guide the development of new vaccines based on the immunological mechanism of anthrax toxin, and use new materials and technologies to detect different aspects of development of anthrax toxins, etc.